2019
DOI: 10.1136/bmjopen-2018-027817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brain training on brain blood flow (The Cognition and Flow Study—CogFlowS): protocol for a feasibility randomised controlled trial of cognitive training in dementia

Abstract: IntroductionCognitive training is an emerging non-pharmacological treatment to improve cognitive and physical function in mild cognitive impairment (MCI) and early Alzheimer’s disease (AD). Abnormal brain blood flow is a key process in the development of cognitive decline. However, no studies have explored the effects of cognitive training on brain blood flow in dementia. The primary aim of this study is to assess the feasibility for a large-scale, randomised controlled trial of cognitive training in healthy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Both dementia and even its prodromal stage, MCI, are characterized by a reduction in cerebral blood flow ( Mazza et al, 2011 ; Sierra-Marcos, 2017 ). A meta-analysis of twenty-six studies investigating CBF in MCI found overall reduced tissue oxygenation, CBF and velocity in MCI compared to healthy controls ( Beishon et al, 2017 ) and studies are underway investigating the CBF changes that may occur with cognitive stimulation in MCI and dementia ( Beishon et al, 2019 ). Similar findings have been noted in patients with Alzheimer’s disease, with reduced CBF in many cortical regions including temporal ( Sandson et al, 1996 ; Alsop et al, 2000 ; Asllani et al, 2008 ; Yoshiura et al, 2009 ; Ding et al, 2014 ) parietal ( Alsop et al, 2000 ; Johnson et al, 2005 ) and other regions including precuneus, frontal and posterior cingulate cortex ( Alsop et al, 2008 ; Yoshiura et al, 2009 ).…”
Section: Mechanism Of Action: Vagus Nerve Stimulation Increases Cereb...mentioning
confidence: 99%
“…Both dementia and even its prodromal stage, MCI, are characterized by a reduction in cerebral blood flow ( Mazza et al, 2011 ; Sierra-Marcos, 2017 ). A meta-analysis of twenty-six studies investigating CBF in MCI found overall reduced tissue oxygenation, CBF and velocity in MCI compared to healthy controls ( Beishon et al, 2017 ) and studies are underway investigating the CBF changes that may occur with cognitive stimulation in MCI and dementia ( Beishon et al, 2019 ). Similar findings have been noted in patients with Alzheimer’s disease, with reduced CBF in many cortical regions including temporal ( Sandson et al, 1996 ; Alsop et al, 2000 ; Asllani et al, 2008 ; Yoshiura et al, 2009 ; Ding et al, 2014 ) parietal ( Alsop et al, 2000 ; Johnson et al, 2005 ) and other regions including precuneus, frontal and posterior cingulate cortex ( Alsop et al, 2008 ; Yoshiura et al, 2009 ).…”
Section: Mechanism Of Action: Vagus Nerve Stimulation Increases Cereb...mentioning
confidence: 99%
“…The study had research ethics committee approval (Bradford Leeds ref: YH/18/0396), and all study procedures were conducted in accordance with the declaration of Helsinki. The protocol for the study has been published previously [15]. In total, 20 healthy older adults, 24 people living with dementia, and 12 with MCI were recruited to the study.…”
Section: Sample Selection and Study Designmentioning
confidence: 99%
“…In addition, participants underwent an assessment of their neurovascular function using transcranial Doppler ultrasonography measured task-activation. Detailed methods and results from the quantitative phase of the study have been published [14,15]. In brief, participants underwent a ve minute resting baseline recording with continuous monitoring of cerebral blood ow velocity (CBFv, transcranial Doppler ultrasound), blood pressure (BP, Finometer), end-tidal CO 2 (ETCO 2 , nasal capnography).…”
Section: Participants Underwent Assessment Of Cognition (Addenbrooke'...mentioning
confidence: 99%
“…In addition, participants underwent an assessment of their neurovascular function using transcranial Doppler ultrasonography measured task-activation. Detailed methods and results from the quantitative phase of the study have been published [14,15]. In brief, participants underwent a ve minute resting baseline recording with continuous monitoring of cerebral blood ow velocity (CBFv, transcranial Doppler ultrasound), blood pressure (BP, Finometer), end-tidal CO 2 (ETCO 2 , nasal capnography).…”
Section: Sample Selection and Study Designmentioning
confidence: 99%